The GROMACS and NAMD Software Packages Comparison (Communications in Computational Physics, 2006)
The comparable feature analysis of NAMD and GROMACS molecular dynamics packages has been done. The benchmarks of 72 and 128 Dipalmitoylphosphatidylcholine (DPPC)/water have been constructed using a cluster (3GHz-Xeon processors and Myrinet network) and the comparison has been performed using GROMOS87and CHARMM27 force fields modified for lipids with GROMACS and NAMD softwarepackages, respectively. The GROMACS has been displayed as faster than NAMD, likelydue to united-atom character of GROMACS and good implementation features. TheGROMACS reaches saturation and goes to the worst results, the reason of which is thatthe program spends more time on communications between processors.
Keywords: NAMD; GROMACS; molecular dynamics; phospholipid bilayers.